ANALISIS NILAI TAMBAH KELAPA MENJADI KOPRA DI KECAMATAN TELUK SAMPIT KABUPATEN KOTAWARINGIN TIMUR: Muchliandy 1), Suroto 2), Parisa Swasti Rn 3) - Muchliandy Muchliandy; Suroto Suroto (Politeknik Seruyan, 2025)
This study aims to determine the characteristics of copra entrepreneurs in Teluk Sampit District, East Kotawaringin Regency, and how much added value is obtained by copra entrepreneurs from copra processing. The method used is quantitative descriptive with data collection techniques through observation, interviews, and documentation. The author decided to involve the entire population of copra entrepreneurs, consisting of 18 respondents. Respondents were grouped into ages 30-35, 41-45, and 46-50 years, each contributing 22.22% of the total. There were no respondents from the 56-60 age group, but there were some from the 61-65 age group, which was 11.11%. Of the 16 copra entrepreneurs, most were male (88.89%), while 2 were female (11.11%). The majority of copra entrepreneurs in Teluk Sampit District are married. Their business experience averages between 3 to 9 years, which is important for business success. The education of copra entrepreneurs is generally junior high school graduates, with a total of 9 people or 50%. This study shows that the added value of processing coconut into copra in Teluk Sampit District is IDR 2,200 per kilogram of copra. Keywords: Characteristics, Added Value